Answer:
Step-by-step explanation:
Answer: x^2, x<2, 5, 2</=x<4
Step-by-step explanation:
Answer:
a = 1 and b = - 10
Step-by-step explanation:
Expand the right side of the identity
x(ax² - 3x + b) - 3(ax² - 3x + b)
= ax³ - 3x² + bx - 3ax² + 9x - 3b
= ax³ - x²(3 + 3a) + x(b + 9) - 3b
Equate the coefficients of like terms on both sides of the identity
x³ terms → ax³ with x³ ⇒ a = 1
x terms → - x with (b + 9)x ⇒ b + 9 = - 1 ⇒ b = - 10
Answer:
2 and 7/8
Step-by-step explanation:
3 + 3/8 - 1/2
3 + 3/8 - 4/8
3 - 1/8
2 and 7/8